2002
DOI: 10.1303/aez.2002.299
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to a mating disruptant composed of (Z)-11-tetradecenyl acetate in the smaller tea tortrix, Adoxophyes honmai (Yasuda) (Lepidoptera: Tortricidae).

Abstract: At tea fields in Shimada in Shizuoka Prefecture, a mating disruptant composed of (Z)-11-tetradecenyl acetate (trade name: Hamaki-con) had been used for controlling Adoxophyes honmai (Yasuda) annually since 1983. In 1986, four years after use of the disruptant was initiated, the disruption percentage of pheromone trap catches was 96%, and a high control effect was observed. However, from 1996 to 1998, 14 to 16 years after treatment was started, the percentages became less than 50%. When the disruptant was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 6 publications
(7 reference statements)
0
34
0
1
Order By: Relevance
“…Ostrinia furnacalis in Asia is an interesting candidate for such an investigation of parallel evolution, since it may result from an independent host shift to maize (Frolov et al 2007). If, as we strongly suspect, geotaxis proves to have evolved as a specific response to harvesting techniques, this would constitute a very singular instance of behavioural resistance to agricultural management techniques other than insecticide application (Levine et al 2002;Mochizuki et al 2002;Miller et al 2009). …”
Section: (B) Behaviours In the Laboratorymentioning
confidence: 99%
“…Ostrinia furnacalis in Asia is an interesting candidate for such an investigation of parallel evolution, since it may result from an independent host shift to maize (Frolov et al 2007). If, as we strongly suspect, geotaxis proves to have evolved as a specific response to harvesting techniques, this would constitute a very singular instance of behavioural resistance to agricultural management techniques other than insecticide application (Levine et al 2002;Mochizuki et al 2002;Miller et al 2009). …”
Section: (B) Behaviours In the Laboratorymentioning
confidence: 99%
“…Recently, Mochizuki et al (2002) reported a resistant strain of the smaller tea tortrix, Adoxophyes honmai, against its mating disruptant, Hamaki-con…”
mentioning
confidence: 99%
“…Hamakicon ® simultaneously disrupted the communications of another tortricid pest species, Homona magnanima, in tea gardens, but could induce the evolution of a resistant strain. This problem has been resolved by a new disruptant, including all components produced by females (Mochizuki et al, 2002). Because mating disruption is a modern and unique technique, it is possible that similar unexpected problems will take place during application in the field.…”
mentioning
confidence: 99%
“…However, use of a single component in mating disruption is less effective than a mixture. In addition, it was demonstrated with another lepidopteran species that continuous use of a single pheromone constituent in mating disruption may lead to "resistance", which can be avoided with a multi-component pheromone system (Mochizuki et al 2002).…”
mentioning
confidence: 99%